Favorable outcome in post-anoxic coma despite bilateral absence of cortical N20: A case report. Issue 1 (January 2019) - Basaldella, F.; Squintani, G.M.; Alessandrini, L.; Arcaro, C.; Tramontano, V.; Romito, S.; Zanoni, T.; Ferlisi, M.; Avancini, G.; Milan, B.; Casartelli, M.; Zanatta, P.
Abstract : Evaluation of the predictive value of SSEPs in post-anoxic brain injury. A 63-year-old man patient was admitted in Neuro ICU for post anoxic coma after cardiac arrest (CA). He was not treated with Hypothermia. Brain CT scan, SSEPs and EEG were respectively performed at admission and after 12 h from the CA. EEG and SSEPs were repeated between 7th and 9th day. MRI study was also performed after 24 days. First neurophysiological evaluation showed the absence of cortical N20 bilaterally and a continuous EEG activity. CT scan did not show any major brain abnormality. On day 3rd the sedation was stopped and the patient recovered consciousness. No sensory-motor or major cognitive deficits were observed. The second neurophysiological battery detected non-specific slow-frequencies EEG abnormalities and severely reduced amplitudes of bilateral cortical N20 potentials (lower than 0.3 μV). Diffuse cortical-subcortical atrophy and bilateral cortical necrosis in pre-/post-sulcus area were also visible at the MRI. Bilateral absence of cortical N20 still represent one of the strongest neurophysiological predictor of poor outcome in post-anoxic coma, with almost 100% specificity. Nevertheless our case stresses the need to apply a multimodality (EEG and SSEPs) neurophysiological strategy in order to reduce false positive SSEPs results caused by regional brain ischemia.